CLINIC AND COURSE OF ACUTE OTITIS MEDIA IN CHILDREN AGAINST THE BACKGROUND OF CHRONIC HEPATITIS B (Journal of Universal Science Research, 2023)
The purpose of this study is to study the features of the clinic and the course of acute otitis media in children with chronic hepatitis B. It is shown that with chronic hepatitis, children under 14 years old with acute otitis media is 60 patients. Of these, 32 patients are boys, and 28 girls. As a result of the analysis of our data, it was found that the most common signs of acute otitis media in children are: ear pain, suppuration, fever, toxicosis, exsicosis. The peculiarity of the clinical manifestation of acute otitis media in children, in our opinion, is primarily associated with both the biological properties of the virus (damage to immunocomponent cells) and the anatomical and physiological characteristics of the child's body. Summarizing, it should be noted that the clinic and the course of acute otitis media in children with CHB are similar to those in uninfected children, that is, when choosing antibiotic therapy, doctors should follow the same recommendations as in the treatment of acute otitis media in immunocomponent children